6.6k views
3 votes
(w^5 z^2 )(−9w^2 z^5)

User Exit
by
5.9k points

1 Answer

6 votes
we have that
(w^5*z^2)*(-9*w^2*z^5)

Multiplying exponential expressions
we know that
w^5 multiplied by w^2 = w^(5 + 2) = w^7
and
z^2 multiplied by z^5 = z^(2 + 5) = z^7

therefore
(w^5*z^2)*(-9*w^2*z^5) =-9*( w^7)*( z^7)
-9*( w^7)*( z^7)=-(3^2)*( w^7)*( z^7)

the answer is
-(3^2)*( w^7)*( z^7

User Ahe
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.